PERFORMANCE ANALYSIS OF ALUMINUM INDUSTRY BASED ON PRODUCT LIFE CYCLE AND MARKET TRENDS - Akbar, Saiqa Ilham; Nurpita, Anisa (International Business Management - Universitas Ciputra, 2019)
This study tries to measure the performance of aluminum and small and medium industries (SMEs) in Yogyakarta which are considered to be underdeveloped. Based on the development of the number of businesses, over the past ten years the number of SMEs has continued to decline. Based on these conditions, this study tries to use the industry life cycle approach and market trends to analyze the position of the aluminum industry in Yogyakarta City in particular and Indonesia in general to measure the performance of the industry. Descriptive analysis results collected through written questionnaires are complemented by content analysis of the results of interviews and focus group discussions (FGD) with stakeholders to get more in-depth information to draw conclusions and provide suggestions for the development of aluminum SMIs in the city of Yogyakarta. The results obtained from this study are the aluminum industry in the city of Yogyakarta is in an early maturity position so it needs a strategy to extend the industrial life cycle. This research is still limited to one industrial center and is discussed from the perspective of SMIs, the next research will produce more comprehensive results with data from several industrial centers and involve large industries to get a more complete view of the relations between industries. This research is one of the few studies that discuss the performance of the industry in terms of product life cycle in Indonesia which is a fairly good approach in developing development strategies and for survival.